HIV resistance to raltegravir - Clavel François (European Journal of Medical Research, 2009)
Abstract Similar to all antiretroviral drugs, failure of raltegravirbased treatment regimens to fully supress HIV replication almost invariably results in emergence of HIV resistance to this new drug. HIV resistance to raltegravir is the consequence of mutations located close to the integrase active site, which can be divided into three main evolutionary pathways: the N155H, the Q148R/H/K and the Y143R/C pathways. Each of these primary mutations can be accompanied by a variety of secondary mutations that both increase resistance and compensate for the variable loss of viral replicative capacity that is often associated with primary resistance mutations. One unique property of HIV resistance to raltegravir is that each of these different resistance pathways are mutually exclusive and appear to evolve separately on distinct viral genomes. Resistance is frequently initiated by viruses carrying mutations of the N155H pathway, followed by emergence and further dominance of viral genomes carrying mutations of the Q148R/H/K or of the Y143R/C pathways, which express higher levels of resistance. Even if some natural integrase polymorphisms can be part of this evolution process, these polymorphisms do not affect HIV susceptibility in the absence of primary mutations. Therefore, all HIV-1 subtypes and groups, together with HIV-2, are naturally susceptible to raltegravir. Finally, because interaction of integrase strand transfer inhibitors with the HIV integrase active site is comparable from one compound to another, raltegravir-resistant viruses express significant cross resistance to most other compounds of this new class of antiretroviral drugs.